Síntese de membrana híbrida de polissufona com óxido de zinco para limpeza de efluentes têxteis - Sousa, Suzanna Rani Cristina Alves de (2023)
Due to the large volume of effluents from the textile industry, which causes environmental contamination of water bodies, it is necessary to carry out treatment for the reuse or correct disposal of these wastewater. This study aims to produce a polysulfone (PSU) membrane with the addition of zinc oxide (ZnO) for the removal of color from simulated textile effluent resulting from dyeing. The phase inversion technique was used for the production of both pure and hybrid membranes. The produced membranes were analyzed using FTIR, XRD, SEM, AFM, Apparent Porosity, and Contact Angle. The diffractogram results of the membranes showed characteristic peaks of PSU. The infrared spectrum of the hybrid membranes indicated bands characteristic of polysulfone overlaid with bands characteristic of ZnO. SEM and AFM analyses revealed an increase in roughness in membranes with the addition of ZnO and alterations in the cross-sectional structures of membranes with zinc oxide. Apparent porosity and contact angle analyses suggested greater wettability of the hybrid membranes. The membranes were successfully obtained, and all removed more than 80% of the color from the simulated effluent, demonstrating potential use for treating textile effluents.